Reflective facilities in Smalltalk-80 - Foote, Brian; Johnson, Ralph E. (1989)
Computational reflection makes it easy to solve problems that are otherwise difficult to address in Smalltalk-80, such futures, and can allow experimentation with new inheritance, delegation, and protection schemes. FulI reflection is expensive to implement. However, the ability to override method lookup can bring much of the power ofreflection to languages like Smalltalk-80 at no cost in efficiency.
Formato de archivo: PDF
Conference proceedings on Object-oriented programming systems ACM: OOPSLA ྕ, pp. 327-335
Keywords: SMALLTALK-80; SMALLTALK